On Kazama-Suzuki Duality between ₖ(₄, ₛᵤb) and = 2 Superconformal Vertex Algebra - Adamović, Dražen; Kontrec, Ana (Symmetry, Integrability and Geometry: Methods and Applications, 2025)
We classify all possible occurrences of Kazama-Suzuki duality between the = 2 superconformal algebra ᴺ⁼²c and the subregular -algebra ₖ(₄, ₛᵤb). We establish a new Kazama-Suzuki duality between the subregular -algebra ₖ(₄, ₛᵤb) and the = 2 superconformal algebra ᴺ⁼²c for c = −15. As a consequence of the duality, we classify the irreducible ₖ₌₋₁(₄, ₛᵤb)-modules.